2021
DOI: 10.3390/ijms22094506
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol-Induced Rat Glioma C6 Cells Death by Triggering Mitochondrial Stress

Abstract: AIM: To investigate the underlying mechanisms of xanthohumol (XN) on the proliferation inhibition and death of C6 glioma cells. METHODS: To determine the effects of XN on C6 cells, cell proliferation and mortality after XN treatment were assessed by SRB assay and trypan blue assay respectively. Apoptotic rates were evaluated by flowcytometry after Annexin V-FITC/PI double staining. The influence of XN on the activity of caspase-3 was determined by Western blot (WB); and nuclear transposition of apoptosis-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Similarly, findings by Yan et al demonstrated that intravenous administration of 3′-daidzein sulfonate sodium improved mitochondrial function after cerebral ischemia/reperfusion injury in rats through the reduction in mitochondrial swelling, elevation in mitochondrial membrane potential, increasing in GSH peroxidase and superoxide dismutase activities, and decreasing in mitochondrial malondialdehyde levels . Moreover, biochanin A plays an important role in preventing mitochondrial dysfunction by attenuating Aβ(25–35)-induced PC12 cell injury and sensitizing prostate cancer cells (DU145 and LNCap) to TRAIL-induced via a mitochondrial-dependent apoptosis pathway. , Another important flavonoid, xanthohumol, exhibited promising function in improving the mitochondrial function and preventing mitochondria form getting impaired with diffused morphology and increased ROS. , Furthermore, phloretin ameliorates arsenic trioxide-induced mitochondrial dysfunction in H9c2 cardiomyoblasts and reduces the mitochondrial trans-membrane potential through inducing the apoptosis of human hepatoma cells SMMC-7721 . In addition, some investigations reported that proanthocyanidins increases the activity of complex I and improves the mitochondrial dynamics through preventing irradiation-induced differentiation of human lung fibroblasts by ameliorating mitochondrial dysfunction .…”
Section: Pathway-based Review Findings and Discussion: Redox Regulati...mentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, findings by Yan et al demonstrated that intravenous administration of 3′-daidzein sulfonate sodium improved mitochondrial function after cerebral ischemia/reperfusion injury in rats through the reduction in mitochondrial swelling, elevation in mitochondrial membrane potential, increasing in GSH peroxidase and superoxide dismutase activities, and decreasing in mitochondrial malondialdehyde levels . Moreover, biochanin A plays an important role in preventing mitochondrial dysfunction by attenuating Aβ(25–35)-induced PC12 cell injury and sensitizing prostate cancer cells (DU145 and LNCap) to TRAIL-induced via a mitochondrial-dependent apoptosis pathway. , Another important flavonoid, xanthohumol, exhibited promising function in improving the mitochondrial function and preventing mitochondria form getting impaired with diffused morphology and increased ROS. , Furthermore, phloretin ameliorates arsenic trioxide-induced mitochondrial dysfunction in H9c2 cardiomyoblasts and reduces the mitochondrial trans-membrane potential through inducing the apoptosis of human hepatoma cells SMMC-7721 . In addition, some investigations reported that proanthocyanidins increases the activity of complex I and improves the mitochondrial dynamics through preventing irradiation-induced differentiation of human lung fibroblasts by ameliorating mitochondrial dysfunction .…”
Section: Pathway-based Review Findings and Discussion: Redox Regulati...mentioning
confidence: 76%
“…160,161 Another important flavonoid, xanthohumol, exhibited promising function in improving the mitochondrial function and preventing mitochondria form getting impaired with diffused morphology and increased ROS. 37,162 Furthermore, phloretin ameliorates arsenic trioxide-induced mitochondrial dysfunction in H9c2 cardiomyoblasts 44 and reduces the mitochondrial trans-membrane potential through inducing the apoptosis of human hepatoma cells SMMC-7721. 163 In addition, some investigations reported that proanthocyanidins increases the activity of complex I and improves the mitochondrial dynamics through preventing irradiation-induced differentiation of human lung fibroblasts by ameliorating mitochondrial dysfunction.…”
Section: Discussion: Redox Regulation and Therapeutic Perspectives Of...mentioning
confidence: 99%
“…The JC-1 staining assay is used to evaluate the function of mitochondria [ 29 ]. JC-1 monomers emit green fluorescence and indicate damaged mitochondria, while JC-1 polymers emit red fluorescence and indicate healthy mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…JC-1 emits red fluorescence when Δψ m is high and green fluorescence when the Δψ m is low. 31 As shown in Figure 3, the in-cell green fluorescence from JC-1 increased after bpyPCN+light treatment, indicating photoinduced depletion of Δψ m by bpyPCN. This change in the Δψ m might be a signature of cell apoptosis.…”
mentioning
confidence: 77%